1978
DOI: 10.1126/science.201.4355.532
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of a Furanocoumarin to Armyworms: A Case of Biosynthetic Escape from Insect Herbivores

Abstract: When the linear furanocoumarin xanthotoxin, found in many plants of the families Rutaceae and Umbelliferae, was administered to larvae of Spodoptera eridania, a generalist insect herbivore, it displayed toxic properties lacking in its biosynthetic precursor umbelliferone. Reduced toxicity observed in the absence of ultraviolet light is consistent with the known mechanism of photoinactivation of DNA by furanocoumarins through ultraviolet-catalyzed cross-linkage of strands. Thus, the ability of a plant to conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
3

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(115 citation statements)
references
References 26 publications
3
109
0
3
Order By: Relevance
“…Starved hyraxes offered P. triradiatus as their only food and then exposed to the sun showed phototoxic symptoms such as apathy, photophobia, and injuries around the eyes and the back 3 to 4 hr after feeding (38). The polyphageous southern armyworm Spodoptera eridania (Noctuidae) dies after eating a diet with 0.1% (fresh weight) xanthotoxin if exposed to UV radiation (39). Some insects prevent UV radiation by living in rolled leaves and survive by feeding on plants with high contents of furanocou-marins (39 (40).…”
Section: Distribution and Ecologic Functions Biochemistry Ofselected mentioning
confidence: 99%
See 1 more Smart Citation
“…Starved hyraxes offered P. triradiatus as their only food and then exposed to the sun showed phototoxic symptoms such as apathy, photophobia, and injuries around the eyes and the back 3 to 4 hr after feeding (38). The polyphageous southern armyworm Spodoptera eridania (Noctuidae) dies after eating a diet with 0.1% (fresh weight) xanthotoxin if exposed to UV radiation (39). Some insects prevent UV radiation by living in rolled leaves and survive by feeding on plants with high contents of furanocou-marins (39 (40).…”
Section: Distribution and Ecologic Functions Biochemistry Ofselected mentioning
confidence: 99%
“…The polyphageous southern armyworm Spodoptera eridania (Noctuidae) dies after eating a diet with 0.1% (fresh weight) xanthotoxin if exposed to UV radiation (39). Some insects prevent UV radiation by living in rolled leaves and survive by feeding on plants with high contents of furanocou-marins (39 (40).…”
Section: Distribution and Ecologic Functions Biochemistry Ofselected mentioning
confidence: 99%
“…In 1978, Berenbaum (83) reported that when the linear furanocoumarin, xanthotoxin (III), was administered to the larvae of the southern armyworm, a low level of toxicity was observed that was greatly enhanced when UV light was shown upon the larvae. She also observed a longer time required for pupation to Downloaded by 34 (86) reported that the angular furanocoumarin, angelicin (IV), reduced the growth rate and the fecundity of the larvae of the black swallowtail butterfly, whereas xanthotoxin was not appreciably toxic to this insect.…”
Section: Furanocoumarinsmentioning
confidence: 99%
“…51 To avoid phototoxicity, some insects roll the leaves and feed on the inside of the leaves, thereby avoiding UV radiation. 52 Specialist insects feeding on furanocoumarincontaining plants (Umbelliferae and Rutaceae) such as swallowtail butterflies detoxify them by P-450 oxygenases. Angular furanocoumarins are more difficult to detoxify than linear ones, 53 and some specialists can feed only on linear furanocoumarin-containing plants.…”
Section: Figurementioning
confidence: 99%